Initial Teacher Training (ITE) and Intercultural Education: How to Prevent Violence Against Migrant Children? - Pavez-Soto, Iskra (2023)
The goal of this article is to analyze the relationship between teacher training needs in the field of interculturality and violence against migrant children with a view to an anti-racist education. Results of a study carried out in two regions of the country are presented: Metropolitan and Valparaíso. Through a qualitative methodology, semi-structured interviews were applied to teachers and professionals who serve the migrant school population. It is concluded that there are discourses that recognize the problems of racism and discrimination suffered by this population, as well as other accounts that deny or minimize it, hierarchizing the nationalities of origin of the migrant student body. There is also an urgent need for teacher training that emerges from a global public policy that promotes an updated curriculum where cultural diversity is a value, while the category of childhood is recognized as a priority axis of inequality and the recognized reception as a transversal practice. In the current scenario, various coexistence conflicts arise that need to be managed from paradigms that are friendly to migrant children and methodologies that recognize their rights and guarantee true inclusion in our country.